2019
DOI: 10.1007/s40093-019-0277-3
|View full text |Cite
|
Sign up to set email alerts
|

Additive effect of cow dung slurry and cellulolytic bacterial inoculation on humic fractions during composting of municipal solid waste

Abstract: Purpose The work aimed to investigate the effect of cow dung and cellulolytic bacteria on humic characteristics during municipal solid waste composting. Four Bacillus isolates (B. subtilis, B. tequilensis, B. venezuelans and B. amyloliquefaciens) sourced from dumpsite soil were formulated as consortium for the study. Methods Four treatments were considered with addition of bulking agents (ratio 1:7:6) to 15 kg MSW. Treatment Cs 1 (control): only MSW, Cs 2 : MSW + cellulolytic bacterial inoculum @ 5 ml (2 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The increase in both HR and HI in the vermicastings is due to the combined action of earthworm-microbes and is also based on the initial chemical composition of different mixture substrates. A recent study also confirmed the positive influence of vemicomposting on humification of cow and pig manure blended with paper wastes [64,65], and other scientific reports projected the highest humification degree in recycling of municipal solid waste blended with cow dung [66]. The high HI during the vermicomposting could also have contributed to the improvement in mineralization and dissolution of organic matter which reflected an increased percentage of humic acid (Pha) in the coprolites.…”
Section: Humificationmentioning
confidence: 59%
“…The increase in both HR and HI in the vermicastings is due to the combined action of earthworm-microbes and is also based on the initial chemical composition of different mixture substrates. A recent study also confirmed the positive influence of vemicomposting on humification of cow and pig manure blended with paper wastes [64,65], and other scientific reports projected the highest humification degree in recycling of municipal solid waste blended with cow dung [66]. The high HI during the vermicomposting could also have contributed to the improvement in mineralization and dissolution of organic matter which reflected an increased percentage of humic acid (Pha) in the coprolites.…”
Section: Humificationmentioning
confidence: 59%
“…Subsequently various undesirable compounds (such as odors and salts) unfavorable for plant development are released (Mohee et al, 2015;Onwosi et al, 2017). A general trend was observed with declined C/N ratio throughout the process attributed to a higher waste degradation (carbon) to mineralization (nitrogen) ratio (Yang et al, 2015;Rastogi et al, 2019a). Hence, to optimize C/N within composting, wide variety of bulking agents are recommended as additives to waste (e.g.…”
Section: A) C/n Ratiomentioning
confidence: 99%
“…Hachicha et al (2012), observed similar results with fungus, Trametes versicolor as an inoculate to the lignocellulosic waste. An investigation on MSW composting by Rastogi et al (2019a), stated the effect of cellulolytic bacterial additives on humic characteristics of waste. The study revealed an early maturity in the inoculated compost, owing to a good humification degree.…”
Section: Em Modified Compost Qualitymentioning
confidence: 99%
“…Cow dung is a rich source of micro ora and very effective in organic waste degradation (Randhawa and Kullar, 2011;Rastogi et al, 2019). Singh and Kalamdhad, (2013) in his composting study used a rotary drum for a mixture of saw dust, vegetable waste, and cow-dung in composting.…”
Section: Introductionmentioning
confidence: 99%
“…The heat microbes produce causes the compost temperature to rise rapidly. Microbes release hydrolytic enzymes which breaks complicated structured molecules promoting faster degradation (Rastogi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%